TEACHER OF TECHNOLOGY AND COMPUTER SCIENCE - EDUCATION IN ADVANCED STUDIES - SAŁATA, Elżbieta (Trends in education, 2008)
General technology education is the important part of general knowledge education. Only good prepared teachers can deliver it. Introduction of two-level studies during which students have such subjects as: technology, computer science and education should be favorable to it.
Keywords: education; technology and computer science education